2014
DOI: 10.3389/fmicb.2014.00038
|View full text |Cite
|
Sign up to set email alerts
|

Associations and dynamics of Vibrionaceae in the environment, from the genus to the population level

Abstract: The Vibrionaceae, which encompasses several potential pathogens, including V. cholerae, the causative agent of cholera, and V. vulnificus, the deadliest seafood-borne pathogen, are a well-studied family of marine bacteria that thrive in diverse habitats. To elucidate the environmental conditions under which vibrios proliferate, numerous studies have examined correlations with bulk environmental variables—e.g., temperature, salinity, nitrogen, and phosphate—and association with potential host organisms. However… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

19
379
3
4

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 326 publications
(405 citation statements)
references
References 187 publications
(304 reference statements)
19
379
3
4
Order By: Relevance
“…The potential for particle attachment is particularly salient in the case of disease-causing species like V. cholerae or V. alginolyticus, which have both been shown to be highly responsive to dust-Fe. These species are known to associate with zooplankton and marine organisms, directly influencing their survival in the environment and routes of transmission to potential hosts (3,9,46). This study, to our knowledge, is the first to demonstrate that Vibrio species, as a model of a rapidly responding opportunistic heterotroph, are highly responsive to Saharan dust-Fe and associated nutrients and indicate a role for these bacteria in processing dust-Fe in marine ecosystems.…”
Section: Discussionmentioning
confidence: 77%
See 3 more Smart Citations
“…The potential for particle attachment is particularly salient in the case of disease-causing species like V. cholerae or V. alginolyticus, which have both been shown to be highly responsive to dust-Fe. These species are known to associate with zooplankton and marine organisms, directly influencing their survival in the environment and routes of transmission to potential hosts (3,9,46). This study, to our knowledge, is the first to demonstrate that Vibrio species, as a model of a rapidly responding opportunistic heterotroph, are highly responsive to Saharan dust-Fe and associated nutrients and indicate a role for these bacteria in processing dust-Fe in marine ecosystems.…”
Section: Discussionmentioning
confidence: 77%
“…Like other opportunistic heterotrophic bacteria, Vibrio can have disproportionately large impacts on carbon and nutrient processing because of their ability to reproduce rapidly and respond to pulses of newly available resources (2,(5)(6)(7). Characterized as "opportunitrophs," Vibrio have a broad genomic and metabolic repertoire (8), allowing them to compete in highly variable nutrient environments ranging from the open ocean to pathogenic associations with animal hosts (3,9). This genus includes many well-known pathogens of marine organisms and humans, and disease incidence has risen sharply in the last 20 y (10,11).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Water temperatures, when integrated over the preceding week, showed that the latter two days belonged to warmer temperature regimes than the first day, where the minimum for the latter was 10.7°C, and the minima for the former were 14.9°C and 14.2° [ Table 3]. Increase in temperature has been shown to be the strongest predictor of increase in total Vibrio abundance, suggesting that growth rates may have been elevated on the latter two days (Oberbeckmann et al, 2012;Takemura et al, 2014). The diversity in unique Vibrio Hsp60 sequences was also higher on the latter two warmer days, when phage predation was greater, than on the first day [ Table 1].…”
Section: Differences In Incidence Of Viral Predation Across Daysmentioning
confidence: 99%